Ataxia-telangiectasia–Mutated Protein Kinase Levels Stratify Patients With Pancreatic Adenocarcinoma Into Prognostic Subgroups With Loss Being a Strong Indicator of Poor Survival. Issue 2 (March 2015) - Kamphues, Carsten; Bova, Roberta; Bahra, Marcus; Klauschen, Frederick; Muckenhuber, Alexander; Sinn, Bruno V.; Warth, Arne; Goeppert, Benjamin; Endris, Volker; Neuhaus, Peter; Weichert, Wilko; Stenzinger, Albrecht
Abstract : Objectives: Recently, aberrations in the gene encoding for ataxia-telangiectasia–mutated (ATM) protein kinase have been reported for pancreatic ductal adenocarcinomas (PDAC). These findings argue that ATM deficiency may play a role during carcinogenesis. Therefore, in this study, we investigated the clinical relevance of ATM expression and ATM activation in PDAC. Methods: Both ATM expression and nuclear phosphoSer1981-ATM levels were assessed by immunohistochemistry in a cohort of 133 PDAC and correlated with clinicopathological parameters. Results: We found stratification in prognostic subgroups. Complete loss of Ser1981-ATM was indicative of the worst prognosis (median survival, 10.8 vs 14.3 months [low expression] vs 31.1 months [high expression], P < 0.001). Similarly, analysis of ATM expression demonstrated absent expression levels of ATM to be associated with dismal prognosis (median survival, 9.6 months), whereas expression of ATM in general was associated with increased survival (17.7 months, P = 0.001). Conclusions: Our analysis shows that both ATM expression and activated ATM are prognostic markers in PDAC with respect to standard clinicopathological parameters. These results suggest that ATM should be further explored as prognostic as well as predictive factor with respect to conventional chemotherapies and for putative synthetic lethal approaches. Abstract : Supplemental digital content is available in the text.